Peningkatan Pertumbuhan Ikan Nila (Oreochromis niloticus) Melalui Pemberian Immunostimulan Ragi Roti (Saccharomyces cereviciae) - Bugis, Achmad A; Manoppo, Henky (Universitas Sam Ratulangi, 2014)
This research aimed to examine the effect of baker’s yeast as immunostimulant on growth of nile tilapia and to find out a proper dose of baker’s yeast that promoted optimal growth of fish. Juveniles with an average weight of 31.83 g were obtained from stock available at Aquaculture Study Program of the Faculty of Fisheries and Marine Sciences. This research was conducted at the experimental ponds located at the Faculty of Fisheries and Marine Sciences for three months. During the experiment, fish was fed with pellet supplemented with baker’s yeast as treatment for four weeks as much as 4%/bw/day, twice daily. The doses of baker’s yeast consisted of 0, 10, 20, 30, and 40 g/kg pellet. Fish growth including absolute and relative growth was measured at two weeks interval. Research results showed that after two weeks of feeding, supplementation of baker’s yeast did not affect the growth of fish but after four weeks of feeding, supplementation of baker’s yeast significantly increased fish growth. Fish fed pellet supplemented with 10 g baker’s yeast displayed the highest growth. As conclusion, supplementation of baker’s yeast in fish food could enchance the growth of fish. Keywords: Oreochromis niloticus, immunostimulant, baker’s yeast, growth